Os pilares da arqueologia sul-rio-grandense (1870-1958) - Mergen, Natália Machado (Universidade do Vale do Rio dos Sinos, 2020)
The thesis proposes an analysis about the first archaeological researches carried out in the State of Rio Grande do Sul. The main objective is to bring together and characterize the studies and researchers that produced archeological knowledge between the years 1870 and 1958, recognizing the factors that guided these researches and the outlines that shaped the development of archeological discipline. The analysis of the sources revealed three major movements in this context. The first one occurred between the end of the 19th century and the beginning of the 20th century and was linked to the work of foreigners, mainly of German origin, whose research approached the problems faced at the European level and by the large national institutions. The second was perceived between the 1920s and 1950s and was associated with the activities of the Instituto Histórico e Geográfico do Rio Grande do Sul, where archeology approached and adapted to the historiographic conceptions defended by the institution. The third one extended to the prelude to the Programa Nacional de Pesquisas Arqueológicas in 1965 and was mainly based on the construction of syntheses and reviews of old research, with the aim of exposing new research problems.
Keywords: História da arqueologia; Rio Grande do Sul; Intelectuais; IHGRGS; History of archaeology; Intellectuals; ACCNPQ::Ciências Humanas::História